Latent Variables in a Travel Mode Choice Model: Attitudinal and Behavioural Indicator Variables - Maria Vredin Johansson; Tobias Heldt; Per Johansson (Uppsala University, Department of Economics, 2005)
In a travel mode choice context, we use survey data to construct and test the significance of five individual specific latent variables environmental preferences, safety, comfort, convenience and flexibility - postulated to be important for modal choice. Whereas the construction of the safety and environmental preference variables is based on behavioural indicator variables, the construction of the comfort, convenience and flexibility variables is based on attitudinal indicator variables. Our main findings are that the latent variables enriched discrete choice model outperforms the traditional discrete choice model and that the construct reliability of the attitudinal latent variables is higher than that of the behavioural latent variables. Important for the choice of travel mode are modal travel time and cost and the individuals preferences for flexibility and comfort as well as her environmental preferences.
urn:nbn:se:uu:diva-211062
Keywords: C35; R41; 330; Modal choice; latent variable; discrete choice model; modal safety; Verkehrsmittelwahl; Multivariate Analyse; Diskrete Entscheidung